US guided corticosteroid injection into the subacromial-subdeltoid bursa: Technique and approach - Molini, L. (Elsevier, 2012)
Local injection of cortisone derivatives, sometimes combined with local anesthetics, is frequently administered in rheumatology as the treatment of choice in para-articular diseases or as an adjuvant to systemic therapy in the treatment of arthritis. One of the most frequent local corticosteroid injections administered in daily clinical practice by rheumatologists, orthopedic surgeons, physiatrists, sports medicine doctors and general practitioners is injection into the subacromialsubdeltoid bursa in the treatment of bursitis and anterior superior impingement syndrome of the shoulder. Before local corticosteroid injection is administered, it is important to identify possible contraindications and to examine the documentation provided by the patient. Absolute contraindications or those related to the procedure should be evaluated by the prescribing physician but also the physician performing the corticosteroid injection should evaluate possible contraindications to make sure that corticosteroid injection is feasible. The present paper describes the ultrasound (US) guided local corticosteroid injection procedure with particular attention to the equipment required, the position of the patient and the examiner as well as the approach. The main advantage of US guidance during corticosteroid injection is the possibility to identify vascular structures, nerves and tendons situated in the needle path in order to avoid these structures and be sure to inject the drug into the appropriate location. When all rules are complied with and the corticosteroid injection is carried out by an experienced physician, it is virtually painless and is performed in just a few minutes.